Pojęcie polityki inwestycyjnej gminy - Goleń, Marek J. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aims of the paper are: to define the concept of the commune's investment policy through the analysis of the concepts of policy, investments and commune; to locate the commune's investment policy in the general commune's and country's economic policy; and to describe the commune's tasks in the county's investment policy on the basis of the commune's self-government act as well. The paper concentrates on the theoretical reflection of the subject. The practical problems of the investment policy has been in principle passed over. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 285-296